Association between renal function and chemotherapy-related toxicity in older adults with cancer. Issue 2 (March 2017) - Peterson, Lindsay L.; Hurria, Arti; Feng, Tao; Mohile, Supriya G.; Owusu, Cynthia; Klepin, Heidi D.; Gross, Cary P.; Lichtman, Stuart M.; Gajra, Ajeet; Glezerman, Ilya; Katheria, Vani; Zavala, Laura; et al.
Abstract: Purpose: To evaluate the association between renal function (RF) and chemotherapy-related toxicity (CRT) in older adults with cancer and to compare the effect of different RF formulas and body weight measurements on this association. Methods: This is a secondary analysis of data from a prospective multicenter study of patients ≥ age 65 who were starting a new chemotherapy regimen. RF was estimated with 4 formulas (modified Jelliffe [Jelliffe], Cockcroft–Gault [CG], Wright, and Modification of Diet in Renal Disease [MDRD]), using actual, ideal and adjusted body weights for 492 patients. The association between baseline RF and grade 3–5 CRT was evaluated by unconditional logistic regression. Results: As a continuous variable, decreased creatinine clearance (CrCl) calculated by CG with actual body weight was associated with increased odds of CRT (OR 1.12, P < 0.01; 95% CI 1.04–1.20) indicating that on average for every 10 mL/min decrease in CrCl the odds of CRT increased by 12%. Very low RF (in the lowest 10%) with all formulas (CG, Jelliffe, Wright and MDRD) was associated with increased odds for CRT. This association is independent of the type of chemotherapy received (those requiring dose adjustment for renal function vs not). Neither primary dose reduction nor chemotherapy duration was associated with CRT. Serum creatinine alone was not associated with increased odds of CRT (OR 0.67, P = 0.15). Conclusions: Decreased RF is associated with increased odds of CRT and should be considered when assessing risk of CRT in older adults with cancer. Serum creatinine alone is not adequate for risk assessment.